Cloze technique for development of reading in foreign language learning english In students of the faculty of law - Solís-Barrueta, Aleacib (2019)
The present research studies the problem of whether or not signicant differences in reading comprehension in students of the subject of English II at the Faculty of Law and Political Science at the University of Huánuco 2013-II, a group working with the cloze technique , with respect to the group of students which does not apply this technique. The hypothesis formulated is "The Technical CLOZE inuences on the development of reading comprehension in learning English Foreign Language students of the Second Cycle of the Faculty of Law and Political Science at the University of Huánuco 2013-II". The study population consisted of 160 students in the second cycle of the Faculty of Law and Political Science, which was extracted a sample of 39 students. Test was administered at the inferential reading comprehension using pretest and post-test, the sample randomly assigning two groups: experimental and control. The results indicate that the initial reading comprehension scores of the study sample were low, as students correctly answered no inferences raised. But after research conducted experimental, it was observed that there was signicant difference in reading comprehension level of the student group that was treated "Application of cloze technique", in relation to the group to which it was applied that treatment, as the percentage difference between these two groups after post-test was 55.19%, appreciating that there was a better performance in reading comprehension in the experimental group. In conclusion, the application of "Cloze technique" has signicantly improved the experimental group's reading comprehension.